THE NATURE OF CHANGES IN THE ELDERLY'S PERSONALITY FEATURES DURING THE POSTEMPLOYMENT PERIOD - Nataliya V. Frolova; Alina Hr. Chetveryk-Burchak (Alfred Nobel University Publisher, 2022)
The article presents the results of the theoretical and methodological substantiation and empirical verification of the approach to investigation the changes in elderly's personality features during postemployment period. Theoretical analysis revealed that professional activity should be considered as the significant predictor of differences in perception and adaptation of the elderly. To meet the purpose of the study the sample of research participants was split into two subgroups (employed and unemployed seniors) to reveal changes in their personality features. Results of the empirical study confirmed the significant differences in dispositional traits and other personality features among groups of employed and unemployed seniors (adaptation, self-perception, acceptation of other people, internality, dominance, time orientation, autonomy, spontaneity, self- understanding, autosympathy, sociability, flexibility in communication, self-actualization appeared to be higher among employed seniors comparing to unemployed). Employed elderlies also showed higher level on such scales as: extraversion, agreeableness, self-control, emotional stability, expressiveness in comparison to the group of unemployed ones. The group of unemployed seniors tend to experience higher level of emotional comfort, but at the same time they are characterized by high level of anxiety, frustration, loneliness, aggression and rigidity. The multiple correlation-regression analysis yielded the following hierarchy of the most informative aspects of the elderly's adaptation. They include: spontaneity and self-realization. The findings open up new prospects for identifying the potential personality precursors of adaptation of the elderly people.